Within-ejaculate sperm competition. (7th December 2020) - Sutter, Andreas; Immler, Simone
Abstract : Sperm competition was defined by Geoff Parker 50 years ago as the competition between sperm from two or more males over the fertilization of a set of eggs. Since the publication of his seminal paper, sperm competition has developed into a large field of research, and many aspects are still being discovered. One of the relatively poorly understood aspects is the importance of selection and competition among sperm within the ejaculate of a male. The sheer number of sperm present in a male's ejaculate suggests that the competition among sibling sperm produced by the same male may be intense. In this review, we summarize Parker's theoretical models generating predictions about the evolution of sperm traits under the control of the haploid gamete as opposed to the diploid male. We review the existing evidence of within-ejaculate competition from a wide range of fields and taxa. We also discuss the conceptual and practical hurdles we have been facing to study within-ejaculate sperm competition, and how novel technologies may help in addressing some of the currently open questions. This article is part of the theme issue 'Fifty years of sperm competition'.